The meaning of "Thy will be done": An investigation into prayer - Kroesbergen, Hermen (HTS teologiese studies, 2015)
This article investigates how we should understand the prayer ‘But thy will not mine be done’, using Wittgenstein’s ordinary language approach. The later Wittgenstein argued that philosophy’s task is to assemble reminders of how language is used in daily life for a particular purpose. This approach offers a way to understand how, despite what theologians have argued, ‘Thy will be done’ is neither making prayer useless, nor is it fundamental to all petitionary prayers. Firstly, the framework and method of Wittgenstein’s ordinary language will be explained. Secondly, reminders will be assembled for the purpose of showing that the prayer ‘Thy will be done’ does not need to make praying useless. Thirdly, the appropriate reminders to refute the statement that ‘Thy will be done’ is fundamental to all petitionary prayers will be presented. And, finally, these two sets of reminders will be connected to one another to provide a more truthful understanding of the prayer ‘Thy will be done’.